UV Radiation Induces Specific Changes in the Carotenoid Profile of Arabidopsis thaliana - Badmus, Uthman O; Crestani, Gaia; Cunningham, Natalie; Havaux, Michel; Urban, Otmar; Jansen, Marcel A K (Biomolecules, 2022)
UV-B and UV-A radiation are natural components of solar radiation that can cause plant stress, as well as induce a range of acclimatory responses mediated by photoreceptors. UV-mediated accumulation of flavonoids and glucosinolates is well documented, but much less is known about UV effects on carotenoid content. Carotenoids are involved in a range of plant physiological processes, including photoprotection of the photosynthetic machinery. UV-induced changes in carotenoid profile were quantified in plants (Arabidopsis thaliana) exposed for up to ten days to supplemental UV radiation under growth chamber conditions. UV induces specific changes in carotenoid profile, including increases in antheraxanthin, neoxanthin, violaxanthin and lutein contents in leaves. The extent of induction was dependent on exposure duration. No individual UV-B (UVR8) or UV-A (Cryptochrome or Phototropin) photoreceptor was found to mediate this induction. Remarkably, UV-induced accumulation of violaxanthin could not be linked to protection of the photosynthetic machinery from UV damage, questioning the functional relevance of this UV response. Here, it is argued that plants exploit UV radiation as a proxy for other stressors. Thus, it is speculated that the function of UV-induced alterations in carotenoid profile is not UV protection, but rather protection against other environmental stressors such as high intensity visible light that will normally accompany UV radiation.
Keywords: carotenoid; photosynthesis; xanthophyll; Ultraviolet Rays; UV-B; chromozomální proteiny, nehistonové; Arabidopsis Proteins; photoreceptor; ultrafialové záření; Photosynthesis; arabidopsis; Carotenoids; karotenoidy; Chromosomal Proteins, Non-Histone; Arabidopsis; fotosyntéza; proteiny huseníčku